Identification of Wnt responsive genes using a murine mammary epithelial cell line model system - Taneyhill, Lisa (BioMed Central, 2004)
BACKGROUND: The Wnt/Wg pathway plays an important role in the developmental program of many cells and tissues in a variety of organisms. In addition, many Wnts and components of their downstream signaling pathways, such as β-catenin and APC, have been implicated in tumorigenesis. Over the past years, several genes have been identified as Wnt responsive, including c-myc, siamois, and cyclin D1. RESULTS: In order to identify additional genes responsive to Wnt signaling that contribute to the transformed phenotype, we performed a cDNA subtractive hybridization screen between a mouse mammary epithelial cell line that overexpresses Wnt-1 (C57MG/Wnt-1) and the parental cell line (C57MG). The screen identified a total of 67 genes to be up-regulated in response to Wnt signaling. Of these 67 genes, the up-regulation of 62 was subsequently confirmed by Northern and dot blot analyses (and, for a subset, semi-quantitative PCR) of RNA isolated from C57MG cells subjected to (1) an independent Wnt-1 retroviral infection, and (2) co-culture with Wnt-1 expressing cells. Among the confirmed Wnt-1 responsive genes, we further characterized a mouse homolog of the human transcription factor Basic Transcription Element Binding protein 2 (BTEB2), Wnt-1 Responsive Cdc42 homolog (Wrch-1), and Wnt-1 Induced Secreted Protein (WISP-1). CONCLUSION: Several novel genes were identified in this screen, as well as others that have been shown previously to be regulated by Wnt signaling, such as connexin43. The results indicate that cDNA subtractive hybridization is a useful method for identifying genes involved in the process of Wnt-1-induced transformation.